2020
DOI: 10.3390/ijms21051609
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Mode of Action of Vasorelaxant Synthetic Polyoxygenated Chalcones

Abstract: Polyphenols consumption has been associated with a lower risk of cardiovascular diseases (CVDs) notably through nitric oxide (NO)- and estrogen receptor α (ERα)-dependent pathways. Among polyphenolic compounds, chalcones have been suggested to prevent endothelial dysfunction and hypertension. However, the involvement of both the NO and the ERα pathways for the beneficial vascular effects of chalcones has never been demonstrated. In this study, we aimed to identify chalcones with high vasorelaxation potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Vasorelaxants are drugs that can cause dilation of blood vessels that ensure the flow of blood through the vessels at ease—most of these cause relaxation of vascular smooth muscles—the most common method of treatment used for hypertension ( Herradón et al, 2007 ). It has been reported that plant-based compounds like chalcones inhibit angiotensin-converting exam (ACE) through nitric oxide (NO)- and estrogen receptor α (ERα)-dependent pathways to bring about vasorelaxation and lower the risk of CVDs ( Legeay et al, 2020 ). Agastache mexicana (Kunth.)…”
Section: Activity Of Lamiaceae In Cvdmentioning
confidence: 99%
“…Vasorelaxants are drugs that can cause dilation of blood vessels that ensure the flow of blood through the vessels at ease—most of these cause relaxation of vascular smooth muscles—the most common method of treatment used for hypertension ( Herradón et al, 2007 ). It has been reported that plant-based compounds like chalcones inhibit angiotensin-converting exam (ACE) through nitric oxide (NO)- and estrogen receptor α (ERα)-dependent pathways to bring about vasorelaxation and lower the risk of CVDs ( Legeay et al, 2020 ). Agastache mexicana (Kunth.)…”
Section: Activity Of Lamiaceae In Cvdmentioning
confidence: 99%